Patterns of illegal wildlife trade: Characterisation of environmental law violations and wildlife seizures in Portugal, 2003-2019 - Martins, Mariana Tavares (2021)
An accelerated decline of biodiversity and species loss has been observed over the last decades. However, the illegal global wildlife trade, which is paramount for exacerbating the problem, continues to grow. The characteristics and trends of illicit wildlife trade are of undeniable relevance as the development of targeted enforcement strategies and preventive interventions require comprehensible knowledge of the specific wildlife trade dynamics in a particular region. In Portugal, the study of wildlife seizures and environmental law violations is virtually non-existent. To better understand the problem's dimension, we herein retrospectively analysed the wildlife and environmental law contraventions reported in the country to the National Institute for Nature Conservation and Forests, I. P. (ICNF), between 2003 and 2019. From the 3,202 cases of wildlife seizures and environmental law violations analysed during this period, 16.6% concerned cases that fell under the Berne Convention on the Conservation of European Wildlife and Natural Habitats, 47.3% fell under the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), 2.7% of the cases were violations of the Natura 2000 directives, and 0.8% were Ilex aquifolium law-related violations. During the study period, the number of such reports peaked in 2012 (426 cases; 13.3%), the majority of violations being reported by the National Republican Guard (2,043 cases; 63.8%). The most seized taxonomic class was birds (791 cases; 47.6% of the cases for which this information was available) – which comprised an assortment of exotic (e.g., Psittacus Erithacus) and native species (e.g., Carduelis carduelis), followed by reptiles and their parts and derivates (242 cases; 14.6%) and ivory (207 cases; 12.4%). Of note, I. aquifolium, protected in Portugal since 1989 (DL No. 423/89), was the most relevant plant species apprehended (25 cases; 26.9%). Despite Portugal being considered one of the primary exporters of European eel, only 5 apprehensions (23.8% of fish cases) were reported during the study period. Most of the law infractions with administrative decision resulted in the administrative abandonment of the prosecution, as the cases were dismissed (802 cases; 44.3%) or a fine was applied (865 cases; 47.8%) – corresponding to an overall amount of 1,026,038.75 euros; mean value per case of 1,214.24 euros (only 28.9% of which was paid). Only 86 cases (4.7%) followed to a court trial. Effective enforcement policies and interventions should be strengthened, and initiatives to promote change in consumers' behaviour should be implemented. This work aims to depict the areas where further work should be done with additional investment, increasing studies and continuous training of the enforcement agents in the interest of improving interventions and enforcement.